The vitamin D and calcium controversy: an update. Issue 2 (March 2019) - Lewis, Joshua R.; Sim, Marc; Daly, Robin M.
Abstract : Purpose of review: Calcium and vitamin D supplementation is widely recommended for prevention of falls and fracture, particularly in the elderly where calcium intakes and vitamin D levels are often inadequate. A number of meta-analyses have questioned the benefits of untargeted or 'holistic' supplementation for falls and fracture, and raised the possibility of adverse cardiovascular effects. This review provides an update on these controversies. Recent findings: Recent advances have largely centred around new trials of vitamin D and meta-analyses of published trials and observational studies. These articles have identified holistic vitamin D supplementation with or without calcium is unlikely to be an effective primary prevention strategy for falls or fracture. There has also been high-quality evidence that vitamin D, daily or as a bolus, does not reduce the risk of cardiovascular events. Summary: The benefits of vitamin D and calcium supplements for holistic fall and fracture prevention remain uncertain. Recent evidence supports the concept that high-dose vitamin D has adverse musculoskeletal effects. Future studies should focus on moderate daily doses. Finally, there remain inconsistent findings for adverse cardiovascular effects of calcium supplements with or without vitamin D. This uncertainty should be taken into account when evaluating the risk/benefits of supplementation.